Inuksuk: Icon of the Inuit of Nunavut - Graburn, Nelson (Études/Inuit/Studies, 2004)
AbstractThe Inuit of the Canadian Arctic have long been known to the outside world through the accounts of explorers, whalers, traders, and missionaries. Famous for their igloos, dog sleds, kayaks and skin clothing, they became the quintessential hardy people of the American Arctic as portrayed in the film “Nanook of the North.” Now that they have emerged with their own agency in the world, their iconic distinctiveness is threatened by their near disuse of these traditional markers. In the past few years, the Inuit have combined their visibility to outsiders with their pride in heritage to select and foreground a few items, such as the inuksuk, the qulliq and the amautik, which have gone from the ordinary to the extraordinary. This paper explores the emergence of the inuksuk as an icon both for and of the Inuit in Canada, and considers its development, reintegration, commercialization and diaspora.